Cyclic Diguanylate Inversely Regulates Motility and Aggregation in Clostridium difficile - Purcell, Erin B. (American Society for Microbiology, 2012)
Clostridium difficile-associated disease is increasing in incidence and is costly to treat. Our understanding of how this organism senses its entry into the host and adapts for growth in the large bowel is limited. The small-molecule second messenger cyclic diguanylate (c-di-GMP) has been extensively studied in Gram-negative bacteria and has been shown to modulate motility, biofilm formation, and other processes in response to environmental signals, yet little is known about the functions of this signaling molecule in Gram-positive bacteria or in C. difficile specifically. In the current study, we investigated the function of the second messenger c-di-GMP in C. difficile. To determine the role of c-di-GMP in C. difficile, we ectopically expressed genes encoding a diguanylate cyclase enzyme, which synthesizes c-di-GMP, or a phosphodiesterase enzyme, which degrades c-di-GMP. This strategy allowed us to artificially elevate or deplete intracellular c-di-GMP, respectively, and determine that c-di-GMP represses motility in C. difficile, consistent with previous studies in Gram-negative bacteria, in which c-di-GMP has a negative effect on myriad modes of bacterial motility. Elevated c-di-GMP levels also induced clumping of C. difficile cells, which may signify that C. difficile is capable of forming biofilms in the host. In addition, we directly quantified, for the first time, c-di-GMP production in a Gram-positive bacterium. This work demonstrates the effect of c-di-GMP on the motility of a Gram-positive bacterium and on aggregation of C. difficile, which may be relevant to the function of this signaling molecule during infection.